Assessing the Impact and Utilization of Three-Wheeled Cargo Motorcycles by MSMEs in Central Java - Mege, Stacia Reviany; Windriya, Anafil; Werdania, Riandhita Eri; Budiyono, Budiyono (Journal of Vocational Studies on Applied Research, 2023)
The increasing number of Micro, Small, and Medium Enterprises (MSMEs) has led to a high demand for transportation to support business operations. This is particularly true for the use of three-wheeled cargo motorcycles, which are widely used by MSME actors, especially in the Central Java region. This study focuses on eight regions where MSMEs operate: Semarang, Kendal, Ungaran, Demak, Boyolali, Klaten, Sukoharjo, and Solo. The research aims to identify the differences between three-wheeled motorbikes and pick-up trucks and to determine the level of need among MSME operators for three-wheeled motorbikes as transportation to support their business activities. The author employs a descriptive approach using qualitative methods. The research findings indicate several differences between three-wheeled motorcycles and pick-up trucks in terms of functionality. Three-wheeled motor vehicles are more stable, flexible, economically priced, fuel-efficient, and suitable for transporting small goods over short distances. There is a high level of community demand for the use of three-wheeled motor vehicles to support business operations, particularly for the sale of food and beverages such as fresh milk, tobacco, LPG gas cylinders, gallon mineral water, animal feed, and various agricultural commodities to traditional markets. Additionally, three-wheeled vehicles greatly assist MSME operators in their business operations by offering small-scale cargo transport capacity and facilitating access to regions with limited land availability for roads.